2003
DOI: 10.1186/1476-069x-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Concentrations in 1–3 Year Old Lebanese Children: A Cross-sectional study

Abstract: Background: Childhood lead poisoning has not made the list of national public health priorities in Lebanon. This study aims at identifying the prevalence and risk factors for elevated blood lead concentrations (B-Pb ≥ 100 µg/L) among 1-3 year old children. It also examines the need for universal blood lead screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…In the multivariate logistic analyses, in addition, there was a statistically significant association between father in skilled job and incereased BPb concentration. This tendency did not match those of other studies [15,18,19,31]. In the present study, father’s job were categorized based on the International Standard Classification of Occupations 1988.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In the multivariate logistic analyses, in addition, there was a statistically significant association between father in skilled job and incereased BPb concentration. This tendency did not match those of other studies [15,18,19,31]. In the present study, father’s job were categorized based on the International Standard Classification of Occupations 1988.…”
Section: Discussioncontrasting
confidence: 88%
“…As higher BPb concentrations were observed in male children, factors other than those examined in the present study are likely to have contributed to their lead exposure levels. Although previous studies [13,14,15,18,31] on the relationships between lead exposure and SES did not refer to gender differences, taking gender differences into account could be important in preventive measures against lead toxicity in children. …”
Section: Discussionmentioning
confidence: 99%
“…Pirkle et al (1998) showed that children from lower income families were at risk of elevated BLLs. Nuwayhid et al (2003) reported that children from the lower SES and lower educated families had BLLs 10 lg/dL in comparison with other children who had BLLs \ 10 lg/dL. Jacob et al (2000) revealed that lower SES was associated with elevated BLLs in children aged 5-14 years.…”
Section: Discussionmentioning
confidence: 99%
“…A study of children in Callao and Lima metropolitan area revealed that ingestion of soil and ingestion of modeling clay were associated with elevated blood lead levels in the children (Espinoza et al, 2003). Another study demonstrated that BLLs 10 lg/dL was related with the use of hot tap water for cooking (Nuwayhid et al, 2003). Consumption of tap water from lead pipes is a risk factor associated with elevated BLLs in children as opposed to consumption of bottled water (Leroyer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases of lead exposure involving lead-glazed ceramics and kohl were identified among the 690 children screened in France (Inserm and InVS, 2008) and in neonates in three maternity wards in the surroundings of Paris in 2004 (Yazbeck et al, 2007). Traditional cosmetics, such as surma and kohl, are also associated with high levels of lead exposure in children in the countries where they are frequently used (Al-Saleh et al, 1999;Goswami, 2013;Nuwayhid et al, 2003;Rahbar et al, 2002) and in sporadic cases in the US (CDC, 2004(CDC, , 2013b.…”
Section: Cosmetics and Ceramicsmentioning
confidence: 97%